Screen Media and the Construction of Nostalgia in Post-Socialist China - Gu, Zhun. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This book traces the cultural transformation of nostalgia on the Chinese screen over the past three decades. It explores how filmmakers from different generations have engaged politically with China's rapidly changing post-socialist society as it has been formed through three mutually constitutive frameworks: political discourse, popular culture and state-led media commercialisation. The book offers a new, critical model for understanding relationships between filmmakers, industry and the State. Zhun Gu was awarded a Ph.D. by the University of Nottingham in December 2019 and is now a research assistant working at Fudan University. His research focuses on memory studies and intercultural communication in Chinese screen media.
Introduction -- Chapter 1: Nostalgia and Guilt in "Educated Youth" Films: Xie Fei's A Mongolian Tale (1995) and Huo Jianqi's Nuan (2003) -- Chapter 2: Nostalgia for a Communal Lifestyle in Urban Films: Shower (1999) and 24 City (2008) -- Chapter 3: An Ahistorical Nostalgia on Youth Screen: So Young (2013), With You (2016) and Better Days (2019) -- Chapter 4: Rhetoric of Nostalgia from the Harmonious Society to the Community of Shared Future -- Conclusion.
Keywords: Ethnology; Culture; Culture -- Study and teaching; Mass media and history; Motion pictures -- Asia; Regional Cultural Studies; Cultural Studies; Media and Communication History; Asian Film and TV